Answer:
<h2><u><em>
x = 69°</em></u></h2><h2><u><em>
V = 103°</em></u></h2>
Step-by-step explanation:
the sum of the interior angles in a triangles is 180°, take away from 180 the know angles (34° and 77°) and you will have your answer
180 - 34 - 77 = 69°
Now we find angle V
The angle V and the angle of 77 ° are on a straight line, so the sum is 180°, from 180° you subtract 77 ° and you have the value of V
180 - 77 = 103 °
Let's solve this question by step by step.
Layout equation.
−104=−8(k+8)
Step 1: Simplify both sides of the equation.
−104=−8(k+8)
−104=(−8)(k)+(−8)(8)(Distribute)
−104=−8k+−64
−104=−8k−64
Step 2: Flip the equation.
−8k−64=−104
Step 3: Add 64 to both sides.
−8k−64+64=−104+64
−8k=−40
Step 4: Divide both sides by -8.
-8k/-8=-40/-8
The answer for this problem is k=5.
Answer:
(d) (4x² +7)(x -3)
Step-by-step explanation:
This polynomial can be factored by factoring pairs of terms.
= (4x³ -12x²) +(7x -21)
= 4x²(x -3) +7(x -3)
= (4x² +7)(x -3)
__
<em>Additional comment</em>
The answer choices suggest we're not interested in irrational or complex factors. The quadratic (4x² +7) could be factored into linear terms involving irrational complex numbers. The form for "difference of squares" would be used for the purpose.
Answer:
The average rate of change is -3.
Step-by-step explanation:
We are given the function:
![f(x)=9-x^2](https://tex.z-dn.net/?f=f%28x%29%3D9-x%5E2)
And we want to find the average rate of change from <em>x </em>= 0 to <em>x </em>= 3.
In other words, we will compute the function at the two endpoints, and then find the slope of the line that crosses the two points.
For our first endpoint at <em>x</em> = 0, our function evaluates to:
![f(0)=9-(0)^2=9](https://tex.z-dn.net/?f=f%280%29%3D9-%280%29%5E2%3D9)
So, our first point is (0, 9).
For our second endpoint at <em>x</em> = 3, our function evaluates to :
![f(x)=9-(3)^2=0](https://tex.z-dn.net/?f=f%28x%29%3D9-%283%29%5E2%3D0)
So, our second point is (3, 0).
Then by the slope formula, our average rate of change will be:
![\displaystyle m=\frac{0-9}{3-0}=\frac{-9}{3}=-3](https://tex.z-dn.net/?f=%5Cdisplaystyle%20m%3D%5Cfrac%7B0-9%7D%7B3-0%7D%3D%5Cfrac%7B-9%7D%7B3%7D%3D-3)